Modification of Carbon Fibre Surfaces by Sulfur‐Fluoride Exchange Click Chemistry. Issue 23 (6th December 2018) - Randall, James D.; Eyckens, Daniel J.; Stojcevski, Filip; Francis, Paul S.; Doeven, Egan H.; Barlow, Anders J.; Barrow, Andrew S.; Arnold, Chantelle L.; Moses, John E.; Henderson, Luke C.
Abstract: The front cover artwork is provided by the groups of Prof. Luke Henderson (Deakin University) and Prof. John E. Moses (La Trobe University). Read the full text of the Communication at 10.1002/cphc.201800789 . Abstract : "Here, we describe the first modification of a carbon surface (in this case carbon fiber) using the sulfur‐fluoride exchange (SuFEx) reaction…" This and more about the story behind the front cover can be found in the Communication at10.1002/cphc.201800789 .